Consumer prevalence, attitude and dietary behavior of online food delivery applications users in Kuwait - Almansour, Fawaz D; Allafi, Ahmad R; Zafar, Tasleem A; Al-Haifi, Ahmad R (Acta Biomedica Atenei Parmensis, 2020)
The objective of this research was to estimate the prevalence, attitude and dietary behavior of online food delivery application users in Kuwait. A survey of 1045 participants found that 87.6% of them have ordered food online by mobile app. Talabat was the most common food delivery application used among participants in Kuwait. Fast food was the most commonly ordered category followed by sweets and pastries. The most important attribute of electronic ordering is speed of delivery followed by ease of ordering. Around 73.6% of the participants use food apps to order dinner, and 76.4% order fast food at late night. The majority of online food delivery application users in Kuwait have unhealthy dietary practices. The results emphasize a serious need for implementing a suitable intervention for stimulating healthy eating behaviors among food delivery application users in Kuwait.